Orchestrating Digital Innovation: The Case of the Swedish Center for Digital Innovation - Holmström, Jonny; Magnusson, Johan; Mähring, Magnus (Communications of the Association for Information Systems, 2021)
In recent years, researchers have paid increasing attention to how firms facilitate and enact digital innovation in networks with diverse actors (i.e., heterogeneous networks). However, while considerable evidence shows that firms can build key capabilities via engaging with external partners, we found few studies on how they orchestrate digital innovation in situations where an academic unit plays a facilitating role in the heterogeneous network. We address this question by focusing on experiences from a national academic initiative, the Swedish Center for Digital Innovation (SCDI). Formed in 2013, the SCDI has adopted an engaged scholarship approach and a combination of activities designed to increase digital innovation capabilities among partner organizations. We argue that acquiring new knowledge through external and internal sources stimulates firms and public sector organizations engaged in digital innovation to integrate such new knowledge with their existing knowledge base. Specifically, we demonstrate how SCDI’s core activities have created increased capabilities for the involved stakeholders, and we offer lessons learned and recommendations for academic units that wish to orchestrate digital innovation.